Commercial bank management - Peter S.Rose (Boston Irwin, 1991)
Banking is an essential industry, and one with many regulations as well as frequent, important changes. Like previous editions, the Fifth Edition is designed to help students understand the field of banking from the perspective of both a bank customer as well as a bank manager. The author provides a well-written description of the banking industry while keeping the text as current as possible.
Donated by: Anvar Hodjaev